Laboratory quality control and patient safety - Gras, Jeremie M. (Berlin ; Boston : De Gruyter, 2017)
'Every clinical laboratory devotes considerable resources to Quality Control. Recently, the advent of concepts such as Analytical Goals, Biological Variation, Six Sigma and Risk Management has generated a renewed interest in the way to perform QC. The objective of this book is to propose a roadmap for the application of an integrated QC protocol that ensures the safety of patient results in the everyday lab routine'--Provided by publisher.
7.1 Practical cases in the establishment of a QC protocol 7.2 Practical situations in dealing with QC rules violation ; 8 The future of laboratory quality control ; 8.1 References ; 9 Sixty-five key messages in laboratory quality control ; Glossary ; Index
Description based on print version record.
Includes bibliographical references.
Master record variable field(s) change: 650
Keywords: Medical laboratories -- Quality control; Medical laboratories -- Safety measures; Patients -- Safety measures; Diagnosis, Laboratory; Clinical Laboratory Services -- standards; Quality Control; Quality Assurance, Health Care -- methods; Patient Safety -- standards; Electronic books